Peningkatan Hasil Belajar Matematika Berbantuan Media Papan Perkalian Pada Siswa Sekolah Dasar - Purwanty, Ratna; Mayasari, Dian (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to improve mathematics learning outcomes with the help of multiplication board media for third-grade elementary school students. The type of research is classroom action research conducted in 2 cycles. Each cycle is divided into four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 20 third-grade students. Data collection techniques were evaluated through tests carried out at the end of each cycle, as well as observation and documentation. Data were collected using student and teacher activity sheets. There was an increase in student learning outcomes, from a class average score of 60 in cycle I, increasing to 81.5 in cycle II. The percentage of classical completeness also increased from 45% in cycle I to 90% in cycle II. The number of students who achieved minimal completeness in cycle I was 9 out of 20 students, and increased to 18 out of 20 students. Teacher activity increased from 79.16% in cycle I to 95.83% in cycle II with the Very Good criteria. It can be concluded that students' mathematics learning outcomes improved through learning assisted by the multiplication board media.